The journal of Amish and Plain Anabaptist studies - Knowledge Bank; Amish and Plain Anabaptist Studies Association (The Ohio State University Knowledge Bank, 2013)
Publishes articles, both theoretical and empirical, about plain Anabaptist groups, including Amish, Apostolic Christian, Brethren, Bruderhof, Hutterite, Russian Mennonite, Swiss Mennonite, and related movements.
Keywords: Anabaptists : Periodicals; Amish : Periodicals; Mennonites : Periodicals; Amish; Anabaptists; Mennonites; Christianity